Case Report: A Difficult-to-Diagnose Case of Hyperinsulinemic Hypoglycemia Surgically Treated After Developing Acute Pancreatitis - Inoue, Chisa; Nishihama, Kota; Hayasaki, Aoi; Okano, Yuko; Hayashi, Akinobu; Eguchi, Kazuhito; Uemura, Mei; Suzuki, Toshinari; Yasuma, Taro; Inoue, Takeshi; Yorifuji, Tohru; Mizuno, Shugo; et al. (Frontiers in Endocrinology, 2021)
The patient is a 28-year-old Japanese man diagnosed with severe congenital hyperinsulinemic-hypoglycemia six months after birth. Clinical records revealed no imaging evidence of pancreatic tumor at the time of diagnosis. Subsequently, he had developmental disorders and epilepsy caused by recurrent hypoglycemic attacks. The patient’s hypoglycemia improved with oral diazoxide. However, he developed necrotizing acute pancreatitis at 28 years of age, thought to be due to diazoxide. Discontinuation of diazoxide caused persistent hypoglycemia, requiring continuous glucose supplementation by tube feeding and total parenteral nutrition. A selective arterial secretagogue injection test revealed diffuse pancreatic hypersecretion of insulin. He underwent subtotal distal (72%) pancreatectomy and splenectomy. There was no intraoperative visible pancreatic tumor. His hypoglycemia improved after the surgical procedure. The histopathological study revealed a high density of islets of Langerhans in the pancreatic body and tail. There were large islets of Langerhans and multiple neuroendocrine cell nests in the whole pancreas. Nests of neuroendocrine cells were also detected in lymph nodes. The pathological diagnosis was grade 1 neuroendocrine tumor (microinsulinomas) with lymph node metastases. This patient is a difficult-to-diagnose case of hyperinsulinemic hypoglycemia surgically treated after developing acute pancreatitis. We believe this is a unique case of microinsulinomas with lymph metastases diagnosed and treated as congenital hyperinsulinemic hypoglycemia for almost 28 years.